Assessing Clinical Outcomes of Metronidazole for Intra-Abdominal Infections When Dosed Every 12 h Versus Every 8 h in a Multi-Center Health System - Sarah Galante; Ramya Castillo; Todd Price; MaiCuc Tran; Stefanie Stramel-Stafford (Antibiotics, 2025)
Background: Metronidazole is the preferred anaerobic agent for empiric treatment of intra-abdominal infections (IAI). Although dosed every 8 h (q8hr), blood concentrations exceed the in vitro minimum inhibitory concentration (MIC) for anaerobic organisms at 12 h (q12hr). A drug shortage of intravenous (IV) metronidazole prompted the conversion to every 12 h dosing in qualifying patients treated for IAI. Objective: To determine efficacy outcomes of metronidazole dosed every 12 h versus every 8 h in patients treated for IAI. Methods: This was a multi-center, retrospective, cohort study of 201 patients from January to July 2021 (q8hr) and January to November 2023 (q12hr) at five hospitals through the greater Houston area. Included patients were adults with a diagnosis of IAI confirmed by radiographic evidence and a white blood count (WBC) > 12,000 cells/µL and/or temperature > 100.4 °F at the time of diagnosis. The primary outcome was clinical cure of IAI, defined as resolution of signs/symptoms of IAI and normalization of WBC or temperature. Results: A total of 201 patients were included, 103 patients in the q8hr group and 98 patients in the q12hr group. Clinical cure of IAI occurred in 72 patients (69.9%) in the q8hr group and 62 patients (63.2%) in the q12hr group (p = 0.318). The median duration of therapy days was similar for both groups (4.0 [4.0–6.0] vs. 4.0 [3.0–6.0] (p = 0.509)). The frequency of clinical failure was higher in the q12hr group (8.7% vs. 21.4%; p = 0.01). Seven patients in the q8hr group and fourteen patients in the q12hr group required escalation of antibiotics due to the need for broader-spectrum antimicrobial therapy by clinical failure definition. Conclusions: There was no difference in clinical cure of IAI with an extended dosing interval. Clinical failure and escalation in antibiotics was higher in the q12h group due to the need for broader-spectrum gram-negative coverage and not related to the need for anaerobic coverage. Findings suggest that every 12 h dosing has similar outcomes.